Tilapia fish waste: An asset for tissue engineering - A review - Shalini Mundra; Preetha J Shetty; Neetha J Shetty (Wolters Kluwer Medknow Publications, 2023)
Fisheries and aquaculture output have exploded due to an alarming increase in consumption due to the global understanding of the nutritional advantages of fish. Inadvertently, the methods produce a massive amount of fish waste, posing a serious environmental threat. Recycling this waste has now become a major point of controversy that must be resolved. It is critical to emphasize the utility of discarded marine by-products for the creation of high-value commodities such as marine collagen (MC), which can be considered a sustainable solution. Because of its biocompatibility, biodegradability, safety, minimal immunogenicity, and low production costs, MC has various benefits over terrestrial collagen. Many academics have recently become interested in the use of MC as a scaffold. This review focuses on the intriguing contribution of MC in the production of MC-based scaffolds.